Enterprise-based HIV/AIDS strategies: Integration through organisational architecture - G. J. Lee; R. Venter; B. Bates (South African Journal of Business Management, 2004)
The management of the HIV/AIDS pandemic has clearly become a core strategic Issue for many organisations, especially in the developing world. However the policies and practices of an HIV/AIDS programme are often less than integrated and strategic in nature, with organisations frequently subscribing to discrete and isolated interventions in imitation of others, or at best instituting a stand-alone policy. One management tool that may serve to help in drawing together and focusing efforts in this regard is an organisational architecture. Organisational architecture has been suggested as an holistic management tool for the delivery of organisational strategies. This article accordingly reviews varied literature on organisational architectures, and then shows how various HIV/AIDS policies and practices might fit into such an architecture. Organisational architecture could be used effectively to organise, integrate and focus the information and efforts connected to the policies and practices surrounding a corporate HIV/AIDS effort.
Keywords: 650